Special Economic Zones : Progress, Emerging Challenges, and Future Directions - Farole, Thomas (World Bank, 2012)
Ask three people to describe a special economic zone (SEZ) and three very different images may emerge. The first person may describe a fenced-in industrial estate in a developing country, populated by footloose multinational corporations (MNCs) enjoying tax breaks, with laborers in garment factories working in substandard conditions. In contrast, the second person may recount the 'miracle of Shenzhen,' a fishing village transformed into a cosmopolitan city of 14 million, with per capita gross domestic product (GDP) growing 100-fold, in the 30 years since it was designated as an SEZ. A third person may think about places like Dubai or Singapore, whose ports serve as the basis for wide range of trade- and logistics-oriented activities. In this book, the author use SEZ as a generic expression to describe the broad range of modern economic zones discussed in this book. But we are most concerned with two specific forms of those zones: (1) the export processing zones (EPZs) or free zones, which focus on manufacturing for export; and (2) the large-scale SEZs, which usually combine residential and multiuse commercial and industrial activity. The former represents a traditional model used widely throughout the developing world for almost four decades. The latter represents a more recent form of economic zone, originating in the 1980s in China and gaining in popularity in recent years. Although these models need not be mutually exclusive (many SEZs include EPZ industrial parks within them), they are sufficiently different in their objectives, investment requirements, and approach to require a distinction in this book.